Insight into endophytic microbial diversity in two halophytes and plant beneficial attributes of Bacillus swezeyi - Gao, Lei; Ma, Jin-Biao; Huang, Yin; Muhammad, Murad; Lian, Hai-Ting; Shurigin, Vyacheslav; Egamberdieva, Dilfuza; Li, Wen-Jun; Li, Li (Frontiers in Microbiology, 2024)
This study utilized high-throughput sequencing to investigate endophytic bacteria diversity in halophytic plants Anabasis truncate (AT) and Anabasis eriopoda (AE) from the Aral Sea region.Following sequence processing, 356 Amplicon Sequence Variants (ASVs) were discovered. The abundance and variety of endophytic bacteria were higher in AT. Bacillota, Pseudomonadota, Actinomycetota, and Bacteroidota constituted the dominant in AE, whereas Pseudomonadota, Actinomycetota, Bacteroidota, and Chloroflexota constituted the dominant in AT. Biomarkers were identified through LEFSe analysis, showing host-specific patterns. PCoA indicated distinct bacterial community structures. Phylogenetic analysis revealed diverse endophytic bacteria, including potential novel taxa. PICRUSt2 predicted diverse functions for endophytic bacteria in halophytes, indicating recruitment of beneficial bacterial taxa to adapt to extreme hypersaline conditions, including plant growth-promoting, biocontrol, and halophilic/tolerant bacteria.Moreover, the evolutionary relationship, metabolic capabilities, and plant beneficial potentials of the Bacillus swezeyi strains, previously isolated from the above two halophytes, were analyzed using comparative genomic and physiological analysis. The B. swezeyi strains displayed versatile environmental adaptability, as shown by their ability to use a wide range of carbon sources and their salt tolerances. B. swezeyi possessed a wide range of enzymatic capabilities, including but not limited to proteases, cellulases, and chitinases. Comparative genomic analysis revealed that despite some variations, they shared genetic similarities and metabolic capabilities among the B. swezeyi strains. B. swezeyi strains also displayed outstanding plant-growth-promoting and antagonistic potentials, offering potential solutions to the global food crisis. This study enhances our understanding of microbial diversity in halophytes on saline-alkali land in the West Aral Sea, shedding light on the halophyte microbiome and its collaboration with hosts in highly hypersaline environments. This study also provides a scientific basis for developing high-quality microbial fertilizers and implementing sustainable agricultural practices.